Le poids de l’instant dans le récit ferroviaire contemporain - Mahigan Lepage (Conserveries Mémorielles)
This article examines the problem of time in three contemporary railroad narratives published in France during the last decade: François Bon’s Paysage fer (2000), Sereine Berlottier’s Ferroviaires (2009) and Arnaud Maïsetti’s La Mancha (2009). Drawing on the notion of “apparatus” (“dispositif”), the author shows how the operation of writing from a train takes place into a series of relations that support one another: the relation between instant and duration, between disorder and order, between the unformed and form, etc. Here is the question that arises: how could one make narrative, i.e. duration and continuity (Jean-Paul Goux), from what first appears to be a chaos of atomized instants or snapshots? The analysis of the texts reveals a subtle process of construction in which the instant gradually settles itself into duration, through the course of a prose that runs constantly ahead of thought. The instant thus takes on the weight of time, maybe even of memory.